Penerapan Tema Arsitektur Perilaku pada Perancangan Perpustakaan Wilayah Provinsi Aceh - Mawaddah, Siti Afifah; Zahriah, Zahriah; Muliadi, Muliadi (Universitas Syiah Kuala, 2024)
The Covid-19 pandemic that occurred at the end of 2019 had a significant impact on the order of people's lives. In the current post-pandemic period, activity habits and behavior cannot be separated from health protocol rules to prevent the recurrence of cases due to the spread of the Covid-19 virus. The Regional Library of Aceh Province is one of the important facilities for the public which has also had an impact from the Covid-19 pandemic. During the Covid-19 Pandemic, the Aceh Regional Library did not serve users and used temporary buildings due to the process of building the Library building. Once finished and usable, there are various design issues that are no longer relevant to the current post-pandemic period. Like the placement of furniture that causes users to not pay attention to health protocols, the ventilation system is not free. The redesign of the Aceh Province Regional Library applies the theme of Behavioral Architecture with the study concepts of Behavior Setting and Personal Space Crowding. This library redesign aims to. Designing the Aceh Province Regional Library which can accommodate activities to access information, learning, research and recreation by following the needs of users whose behavior is in accordance with the Health Protocol rules.